Neutrophils, Crucial, or Harmful Immune Cells Involved in Coronavirus Infection: A Bioinformatics Study - Hemmat, Nima; Derakhshani, Afshin; Bannazadeh Baghi, Hossein; Silvestris, Nicola; Baradaran, Behzad; De Summa, Simona (Frontiers in Genetics, 2020)
The latest member of the Coronaviridae family called SARS-CoV-2 cussing the Coronavirus Disease 2019 (COVID-19). It is now a pandemic disease and threatening global health. Similar to SARS-CoV, this new virus potentially can infect lower respiratory tracts cells and proceeds to severe acute respiratory tract syndrome followed by pneumonia and even death in many nations. The molecular mechanism of the disease has not yet been evaluateduntil now. we analyzed the GSE1739 microarray dataset including ten SARS-positive PBMC and four normal PBMC. Co-expression network analysis by WGCNA suggested that highly preserved 833 turquoise module with genes respectively were significantly related to SARS-CoV infection. ELANE, ORM2, RETN, BPI, ARG1, DEFA4, CXCL1, and CAMPwere the most important genes involved in this disease according to GEO2R analysis as well. The GO analysis demonstrated that neutrophil activation and neutrophil degranulation are the most activated biological processes in the SARS infection as well as the neutrophilia, basophilia, and lymphopenia predicted by deconvolution analysis of samples. Thus, using Serpins and Arginase inhibitors during SARS-CoV infection may be beneficial for increasing the survival of SARS-positive patients. Regarding the high similarity of SARS-CoV-2 to SARS-CoV, using of such inhibitors might be beneficial for COVID-19 patients.